Exclusive enhancement of catalytic activity in Bi0.5Na0.5TiO3 nanostructures: new insights into the design of efficient piezocatalysts and piezo-photocatalysts. Issue 32 (5th June 2020) - Zhao, Zhicheng; Wei, Liyu; Li, Shun; Zhu, Lifeng; Su, Yiping; Liu, Yong; Bu, Yibin; Lin, Yuanhua; Liu, Weishu; Zhang, Zuotai
Abstract : Bi0.5 Na0.5 TiO3 nanospheres show superior piezo-photocatalytic activity in water splitting, Cr(vi ) reduction and degradation of organic pollutants. Abstract : Piezocatalysis and piezo-photocatalysis have recently emerged as promising strategies to address energy and environmental issues through harvesting mechanical energy. Herein, we report that electrical conductivity, rather than piezoelectric coefficient, is more decisive in determining piezocatalytic and piezopotential enhanced photocatalytic activities. The high electrical conductivity of Bi0.5 Na0.5 TiO3 leads to superior piezo-photocatalytic catalytic activity compared to other reported piezocatalysts for water splitting (H2 production of 158 μmol g −1 h −1 ), Cr(vi ) reduction (first-order rate constant of 0.045 min −1 ), and degradation of organic pollutants (first-order rate constant of 0.061 min −1 for RhB) by introducing sunlight and ultrasonic mechanical vibration with a frequency of 20–80 kHz. Furthermore, the mechanical power, vibration frequency, and particle size of the material are important factors to optimize the piezocatalytic and piezo-photocatalytic performance. This work provides a useful guide to design new piezocatalytic or piezo-photocatalytic materials by synergistically considering the electrical conductivity and piezoelectric coefficient.